Perceiving text and image in Apollinaire's calligrammes - Shingler, Katherine (Edinburgh University Press, 2011)
Literary scholars have recently become increasingly interested in the perceptual and cognitive mechanisms involved in reading, and have incorporated scientific research in this area into their critical approaches to texts. This article argues that such an approach is particularly appropriate when authors explicitly engage with the way in which their texts are visually taken in and processed. This is the case with Guillaume Apollinaire, whose calligrammes are informed by a theory of visual-verbal simultaneity stipulating that the reader should be simultaneously aware of both textual and pictorial aspects of the poem. Experimental research in the psychology of reading and picture perception is used to assess this theory of simultaneity, and specifically to challenge Michel Foucault's claim that reading and viewing are mutually exclusive processes. The article concludes by considering further applications of psychological research to word and image studies.